Asksia AI LOGO

Sia

Question
Math
Posted 8 months ago

Create an equivalent expression through combining like terms. After combining, evaluate the simplified expression by substituting the following values. x=5&Y=7x=-5 \& Y=7
3(4x3Y)+10x2Y+Y
3(4 x-3 Y)+10 x-2 Y+Y
Sign in to unlock the answer
Answer from Sia
Posted 8 months ago
Solution by Steps
step 1
Simplify the expression 3(4x3y)+10x2y+y3(4x - 3y) + 10x - 2y + y
step 2
Distribute the 33 in 3(4x3y)3(4x - 3y): 34x33y=12x9y3 \cdot 4x - 3 \cdot 3y = 12x - 9y
step 3
Combine like terms: 12x9y+10x2y+y12x - 9y + 10x - 2y + y
step 4
Simplify further: 12x+10x9y2y+y=22x10y12x + 10x - 9y - 2y + y = 22x - 10y
step 5
Substitute x=5x = -5 and y=7y = 7 into 22x10y22x - 10y
step 6
Calculate: 22(5)10(7)=11070=18022(-5) - 10(7) = -110 - 70 = -180
Answer
-180
Key Concept
Simplifying and substituting algebraic expressions
Explanation
The problem involves simplifying an algebraic expression by combining like terms and then substituting specific values for the variables to evaluate the expression.

Not the question you are looking for? Ask here!

Enter question by text

Enter question by image

Unlock Smarter Learning with AskSia Super!

Join Super, our all-in-one AI solution that can greatly improve your learning efficiency.

30% higher accuracy than GPT-4o
Entire learning journey support
The most student-friendly features
Study Other Question